Development of an online case-based problem-solving module for ESL writing instruction / Nazeera Ahmed Bazari - Nazeera , Ahmed Bazari (2017)
In Malaysia, efforts to increase the quality of students’ learning and achievement, and teachers’ quality of delivery and instruction have been ongoing as documented in the National Education Blueprints 2015-2025. The complex nature of the teaching profession requires problem-solving skills to be instilled in teachers to ensure they are able to face the demands of the teaching profession and increase the quality of their instruction. However, research has shown that higher education has not adequately prepared pre-service teachers with problem-solving skills, pedagogical content knowledge, ability to bridge theory and practice, and to be adequately prepared to teach. Hence, this study is carried out to develop an Online Case-Based Problem-Solving (OCBPS) Module for ESL Writing Instruction to enhance problem-solving skills and other vital skills that can increase the competency of Teaching English as a Second Language (TESL) pre-service teachers. This study adopts the design and developmental research. It is carried out in three phases: needs analysis, design and developmental, and implementation and evaluation. The needs analysis phase obtains the perspectives of 121 TESL pre-service teachers from two universities through surveys on their level of problem solving skills, and their acceptance of using an online case-based learning module in their course curriculum. The design and developmental phase obtain the views of 18 panel experts through the Fuzzy Delphi Method on the design of the OCBPS module specifically the case criteria, curriculum aspects and media design. The module is implemented in an ESL writing methodology course in a Faculty of Education of a public university in the Klang Valley amongst 22 Teaching English as a Second Language (TESL) pre-service teachers. The module is evaluated through surveys, interviews, and pre-and post-reflective essays by the teacher educator and pre-service teachers who participated in the implementation phase. The evaluation focuses on the usability of the module, which includes the technical aspects, strengths, and attitude towards the module, problems, challenges, suggestions, and the effects of implementing the OCBPS module. The needs analysis findings show that the TESL pre-service teachers need a higher level of problem-solving skills. They perceive problem-solving as important in life, for learning and professional purposes. The needs phase found that the pre-service teachers have a high acceptance of case-based learning, and show interest in viewing online cases for problem-solving purposes. The findings for usability indicate that the OCBPS module has the strengths, and the potential of developing vital skills in ESL pre-service teachers like problem-solving skills, pedagogical content knowledge, ability to bridge theory and practice and preparation for teaching amongst others.